Pengolahan Ampas Kopi Arabika (Coffea arabica L.) menjadi Masker Face Pack Powder di Desa Punggur Besar, Kuburaya: Processing of Arabica Coffee Dregs (Coffea arabica L.) into Face Pack Powder Masks in Punggur Besar Village, Kuburaya - Liza Pratiwi; Pratiwi Apridamayanti; Rafika Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Cosmetics are preparations that are popularly used. Face pack is claimed to rejuvenate the skin and remove dirt and excess oil on the skin. Coffee grounds in Punggur Besar Village have only been thrown away and become waste, so a new breakthrough is needed to process coffee grounds so that they can be utilized and not wasted. This PKM activity will be carried out offline using the Health protocol. The purpose of the Community Service Program (PKM) is product innovation by utilizing coffee grounds waste into masks. This PKM activity began with making masks in the laboratory, training activities for making coffee grounds face packs including exposure of material on cosmetic face pack powder treatments, training with health protocols with the number of participants limited to 20 people with a room capacity of 50 people, exposure on labels and face packaging. pack powder, discussion and question and answer. Evaluation and monitoring activities are carried out using a questionnaire (pretest and post-test). The results of the activity showed significant differences in the results of the questionnaire analysis before and after the activity on each question item. The PKM activity targeting PKK women in Punggur Besar Village succeeded in increasing the ability of PKK women in utilizing coffee grounds waste into face pack powder masks. The next activity is expected to be able to provide assistance so that the resulting product obtains a distribution permit so that the coffee grounds face pack powder product can be marketed with a wider market share.